Development of an integrated thermochemical cycle-based hydrogen production and effective utilization - Sorgulu, Fatih; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
In this study, an assessment of a renewable energy-based hybrid sulfur-bromine cycle for hydrogen fuel production and effective utilization is performed since the present era requires lots of hydrogen for fueling many systems. Hydrogen, produced by the hybrid sulfur-bromine cycle, is supplied to the combustion subsystems by blending with natural gas for residential use. Solar and wind energy sources are potentially considered as renewable energies for green hydrogen production. Also, a drying unit is included with an incineration subsystem. A desalination unit is also integrated to produce freshwater for the community. In this way, electricity, heat, and clean water required both for the community and the subsystems are supplied. The integrated system is then assessed in terms of energy and exergy efficiencies. Here, 0.233 kg/s of natural gas and hydrogen blend and 1.338 kg/s of biomass are provided to the system. The energy and exergy efficiencies of the overall system are determined to be 64.43% and 32.24%. & COPY; 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Thermochemical cycle; Solar energy; Wind energy; Efficiency; Biomass; PLANT; Chemistry; Electrochemistry; Energy & Fuels